2014
DOI: 10.3892/etm.2014.1864
|View full text |Cite
|
Sign up to set email alerts
|

Lithium efficacy in bipolar depression with flexible dosing: A six-week, open-label, proof-of-concept study

Abstract: Lithium has a narrow therapeutic index with a subtle balance between effectiveness and adverse effects. Current guidelines recommend the use of lithium as a treatment for acute bipolar depression; however, the therapeutic range for the treatment has not been fully defined. Recently, the adjunctive lower lithium dose in bipolar depression has revealed potential efficacy; however, no study has investigated it predominantly in monotherapy. In this open-label, proof-of-concept study, 31 individuals with bipolar di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 15 publications
(7 citation statements)
references
References 15 publications
(21 reference statements)
0
7
0
Order By: Relevance
“…Exclusion criteria included rapid cycling BD, current substance (including alcohol) abuse or dependence, with the exception of tobacco, previous electroconvulsive therapy, presence of neurological disorders or any medical disorder that could affect the CNS, mental retardation, medications with CNS effects, vitamins and contraindications for MRI scanning 23 .…”
Section: Methodsmentioning
confidence: 99%
“…Exclusion criteria included rapid cycling BD, current substance (including alcohol) abuse or dependence, with the exception of tobacco, previous electroconvulsive therapy, presence of neurological disorders or any medical disorder that could affect the CNS, mental retardation, medications with CNS effects, vitamins and contraindications for MRI scanning 23 .…”
Section: Methodsmentioning
confidence: 99%
“…Lithium, a commonly applied therapeutic agent for depression ( 13 ), has been demonstrated to exert protective effects on neuronal cells both in vitro and in vivo ( 14 ). A previous study has reported that lithium chloride can ameliorate deficits in spatial learning and memory induced by repeated cerebral IR injury by increasing Akt and GSK3β phosphorylation in addition to increasing BDNF expression in hippocampal neurons ( 15 , 16 ).…”
Section: Introductionmentioning
confidence: 99%
“…Of the remaining studies, 73 publications met the inclusion criteria and were further investigated in detail. The search found 16 publications on anticonvulsants [ 14 , 15 , 16 , 17 , 18 , 19 , 20 , 21 , 22 , 23 , 24 , 25 , 26 , 27 , 28 , 29 ], 20 on atypical antipsychotics [ 21 , 30 , 31 , 32 , 33 , 34 , 35 , 36 , 37 , 38 , 39 , 40 , 41 , 42 , 43 , 44 , 45 , 46 , 47 , 48 ], 2 on lithium [ 49 , 50 ], 28 on antidepressants [ 51 , 52 , 53 , 54 , 55 , 56 , 57 , 58 , 59 , …”
Section: Resultsmentioning
confidence: 99%